Comparison of Critical Listening Proficiency of Teacher Candidates in Terms of Several Variables - Kazu, Hilal; Demiralp, Demet (Ani Yayincilik, 2017)
Purpose: The research has been designed to determine the level of critical listening proficiency of the teacher candidates. It aims at finding answers to the following questions: (1) What is the level of critical listening proficiency of teacher candidates? (2) Do the teacher candidates' levels of critical listening proficiency indicate a significant difference in terms of gender, department, or university exam score variables? Research Methods: In this research, the relational screening model, one of the general screening models, has been utilised. Through this model, the pre-service teachers' levels of critical listening proficiency are determined, and these levels are described separately in terms of several variables (such as gender, department, university entrance exam score type). An easily accessible sampling model has been used in sample selection. The sample of the study consists of 672 teacher candidates studying as senior students in their own. The research data were obtained by using the Critical Listening Proficiency Scale, prepared by the researchers. Findings: The findings indicated that the teacher candidates generally have a high level of critical listening proficiency. The teacher candidates in the departments of Turkish and Arts Teaching demonstrated much higher levels of critical listening proficiency in terms of 'attention-preparation' proficiency than the others. Furthermore, the teacher candidates with the verbal score type displayed higher levels of critical listening proficiency. Implications for Research and Practice: In the light of the results of this paper, the following recommendations can be given; the students studying in the departments focusing on mathematical skills should include more studies designed to improve critical listening proficiency in their undergraduate education. In pre-service trainings, many strategies and techniques should be included to improve the teacher candidates' proficiency for Attention-Preparation in critical listening. Considering the year the pre-service teachers are studying in, their critical listening abilities can be determined and the contributions of undergraduate education in this respect can be studied. (C) 2017 Ani Publishing Ltd. All rights reserved
Öğretmen adaylarının eleştirel ninleme yeterliklerinin çeşitli değişkenler açısından karşılaştırılması
Keywords: communication; listening skills; effective listening; critical listening; teacher education